Characterising temporal aspects of residential electricity consumption using statistical learning - Satre Meloy, AP (2019)
Achieving ambitious climate change mitigation targets requires a comprehensive transformation of the energy system. As part of this transformation, early, rapid, and full decarbonisation of the electricity sector is essential. Residential buildings contribute substantially to electricity consumption, so pathways for electricity system decarbonisation similarly depend on accelerated change in the residential sector.